A Template for Power Reform - Newbery, David M. (World Bank, Washington, DC, 2012)
The author argues that since competition is more effective than regulation in promoting efficiency, separating the potentially competitive parts of the industry from the natural monopoly parts that must remain regulated is good public policy. If this "de-integration" is possible, he says, it should be done, or at least the option should be kept open through continued public ownership of the transmission system. And on the question of privatization, he cites recent experience with power sector reform that suggests that efficiency depends more on the form of regulation than on the form of ownership.